Socio-Economic Characteristics Of The Community Around The Source Of The Madampi Spring, Lawa District Muna Regency - Mariana Zainun; LaPanga Mpalasi; Muhammad Saleh Qadri; Eka Rahmatiah Tuwu; Agus Setiawan; Alamsyah Flamin; L.M. Imanuddin (International journal of technology and education research, 2026)
This study aims to identify the socioeconomic characteristics of the community living around the Madampi spring and to determine the extent to which the community benefits from the existence of this spring. This study employs a descriptive method using simple random sampling to determine the sample size. Based on an analysis of the socioeconomic characteristics of the community around the Madampi spring—specifically regarding income, education, length of residence, distance from socioeconomic facilities, and land ownership—two characteristics were found to be less significant in terms of the community’s socioeconomic conditions: income and length of residence. The characteristics that significantly influence the community’s socioeconomic conditions are education, distance from socioeconomic facilities (such as markets, banks, health centers, and others), and land ownership. The land ownership characteristic has a particularly significant impact on the community’s socioeconomic conditions. This is evidenced by the community’s use of vacant land to grow cocoa and oranges, which has now begun to transform and improve the community’s economy.